MTA3 regulates malignant progression of colorectal cancer through Wnt signaling pathway - Taiwei Jiao; Yue Li; Tong Gao; Yining Zhang; Mingliang Feng; Mengyuan Liu; Huan Zhou; Mingjun Sun (Tumor Biology)
MTA3 overexpression has been implicated in carcinogenesis. The aim of the present study was to explore the clinical significance and biological roles of MTA3 in human colorectal cancer and colorectal cancer cells. A total of 80 cases of colorectal cancer tissues were examined by immunohistochemistry for MTA3 protein expression. We analyzed the relationship between MTA3 and clinical factors and the results showed that MTA3 was overexpressed in 51.25% (41/80) cancer cases. There was significant associations between MTA3 overexpression and advanced TNM stage (p = 0.0086) and Ki67 index (p = 0.001). We overexpressed MTA3 in LoVo cells and depleted its expression in HCT15 cells. The results showed that MTA3 promoted cancer cell proliferation, invasion, migration, and cell cycle progression, and inhibited 5-fluorouracil-induced apoptosis in LoVo cell line. MTA3 depletion in HCT15 cell line showed the opposite effects. In addition, we found that MTA3 positively regulated cell cycle proteins including cyclin D1 and cyclin E. It also upregulated Bcl2 and downregulated Bax expression. Furthermore, we found that MTA3 could activate Wnt signaling pathway by upregulating Wnt target proteins. Our results demonstrated that MTA3 overexpression contributes to colorectal cancer carcinogenesis, progression, and chemoresistance. MTA3 could serve as a potential therapeutic target in colorectal cancer.